1992
DOI: 10.1002/hep.1840150322
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenic effects of hepatic stimulator substance on cultured nonparenchymal liver epithelial cells

Abstract: We determined whether hepatic stimulator substance shares its mitogenic specificity for hepatocytes with nonparenchymal epithelial cells in the hepatocyte lineage. Cell lines designated HTC (derived from a rat hepatoma known to respond to hepatic stimulator substance) and FNRL, K-16 and K-22 (derived from rat liver nonparenchymal epithelial cells) were used. After exposure to hepatic stimulator substance, [3H]-thymidine incorporation into DNA was significantly increased (p less than 0.001) in HTC, FNRL and K-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
3

Year Published

1992
1992
2012
2012

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 32 publications
0
21
0
3
Order By: Relevance
“…After 72 hours, 1 Ci 3 H-thymidine was added for 1 hour, and incorporation of thymidine into DNA was analyzed as previously described. 19 Statistical Analysis. Data are presented as the mean Ϯ SD.…”
Section: Methodsmentioning
confidence: 99%
“…After 72 hours, 1 Ci 3 H-thymidine was added for 1 hour, and incorporation of thymidine into DNA was analyzed as previously described. 19 Statistical Analysis. Data are presented as the mean Ϯ SD.…”
Section: Methodsmentioning
confidence: 99%
“…Two hours later, drugs affecting potassium channel activity or vehicle alone was added to cultured cells. Primary rat hepatocytes were cultured with and without 10 ng/ml hHGF and incubated with drugs for 44 -46 h. HepG2, HuH-7, and HFL cells were cultured for 22-23 h. This was followed by the addition of 1 Ci of [ 3 H]thymidine (Sigma) for 1 h. Cells were washed twice with ice-cold phosphate-buffered saline, and trichloroacetic acid-precipitable DNA was extracted as described previously (29). [ 3 H]Thymidine incorporation into DNA was measured by liquid scintillation counting with normalization to DNA content.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have shown the potential of stem cells to differentiate toward hepatocytes. Human mesenchymal stem cells (hMSCs) [8] as well as human embryonic stem cells (hESC) [9], liver stem cells/oval cells [10], cord blood cells [11], bone marrow stem cells [12] and fetal hepatocytes [13] are stem cell types that display potential to develop into hepatocytes. Bone marrow represents an abundant and accessible source of adult stem cells that can differentiate along multiple lineage pathways, including the hepatic lineage [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Other advantages of using mesenchymal stem cells in tissue regenerative medicine include their ease of isolation, proliferative capacity, efficiency of in vitro transfection and the potential use of autologous cells [7]. Many studies have shown the potential of stem cells to differentiate toward hepatocytes [8][9][10][11][12][13]. The traditional concept of stem cell-based therapy consists of the isolation of stem cells from patients, expansion and differentiation in vitro, and subsequent re-transplantation of autologous cells into the patient.…”
Section: Introductionmentioning
confidence: 99%